School-Based Management: Participation in Improving the Quality of Education - Ela, Anastasia; Ismanto, Bambang; Iriani, Ade (Universitas Pendidikan Ganesha, 2023)
Many efforts have been made to improve the quality of education, but education is still faced with various problems, the most crucial of which is the low quality of education. The aims of this study were to evaluate the implementation of school participation in improving the quality of education. This type of research is descriptive evaluative research. The evaluation model used in this study is the discrepancy evaluation model. This study used interview techniques, observation, and document study to collect data. Data acquisition is used with Miles and Huberman analysis. Data validation was obtained by using the data validity triangulation technique. The study results showed that the implementation of the school participation design has been carried out but has yet to meet the standards set by the government. It is because there are no AD/ART and work programs as the basic basis for carrying out activities, the implementation of school participation installations has not been carried out properly because there has not been an allocation of budgetary costs as a supporting facility to support organizational activities, implementation of the school participation process has been carried out, but not all roles have been carried out optimally by schools, implementation of school participation products already exists but is not yet by government standards. Products of school participation that still need evaluation reports on work program quality report cards, namely: budget evaluation results, infrastructure, learning outcomes, meeting minutes, quality report card production unit development documents, and graduate marketing reports.